Chemical composition and cytotoxic activity of Garcinia atroviridis Griff. ex T. Anders. essential oils in combination with tamoxifen - Tan, W.-N. (Taylor and Francis Ltd., 2018)
Garcinia atroviridis Griff. ex T. Anders. is used as a medication agent in folkloric medicine. The present study was to examine the chemical composition of the stem bark and leaf of G. atroviridis as well as their cytotoxic effects against MCF-7 cells. The constituents obtained by hydrodistillation were identified using GC-MS. The stem bark oil (EO-SB) composed mainly the palmitoleic acid (51.9) and palmitic acid (21.9), while the leaf oil (EO-L) was dominated by (E)-Î²-farnesene (58.5) and Î²-caryophyllene (16.9). Treatment of MCF-7 cells using EO-L (100Â Î¼g/mL) caused more than 50 cell death while EO-SB did not induce cytotoxic effect. EO-L has stimulated the growth of BEAS-2B normal cells, but not in MCF-7 cancerous cells. The IC50 of EO-L in MCF-7 and BEAS-2B cells were 71 and 95Â Î¼g/mL, respectively. A combination treatment of EO-L and tamoxifen induced more cell death than the treatment with drug alone at lower doses. Â© 2017 Informa UK Limited, trading as Taylor & Francis Group.